Promalin® (GA4+7 + 6BA) effect on yielding and development of apple fruits cv. Royal Gala - Fioravanço, João Caetano; Almeida, Gustavo Klamer de; Silva, Vanderlei Candido da (Revista de Ciências Agroveterinárias, 2010)
This research evaluated the efficiency of Promalina® on fruit development, russeting incidence and yield of Royal Gala/M-9 apple. It was carried out at Estação Experimental de Fruticultura de Clima Temperado of Embrapa Uva e Vinho, in Vacaria, RS, Southern of Brazil, from August/2007 to February/2008. The experimental design was completely randomized in blocks, in factorial scheme 2 x 4 with 8 treatments, 5 replicates and 1 useful plant per plot. Two application times (1 - at full bloom and 2 - at petals fall) were combined with four concentrations of Promalina® (1 – water (control); 2 – 0.5 ml L-1; 3 - 1.0 ml L-1 and 4 - 2.0 ml L-1). There was no influence of the application time and concentrations of Promalina® on Royal Gala apple production, fruits fresh mass and russeting incidence. Plants treated with Promalina® in petals fall produced fruits with largest length and diameter. Promalina® at 2.0 ml L-1 increased the fruit length and percentage of 65-70 mm diameter class. There was an increase in the C/D rate of the apples with Promalina® application.